A NEW STAGE IN THE DEVELOPMENT OF EDUCATION - Nilufar Sh. Niyozova (Central Asian Journal of Medicine, 2022)
Purpose: to show the features of education in the Republic of Uzbekistan, the democratic nature of the "Law on Education" in the legal framework, types and forms of education and the content of the articles of this Law. Materials and methods: The main material of the article is the Law of the Republic of Uzbekistan "On Education", as well as the Law of the Republic of Uzbekistan "On Combating Corruption" and other sources. Their methods include pedagogical, educational, political and practical aspects. Result: strengthening of the study of the legal framework of education; search for modern learning opportunities in educational institutions; achieving professional development of teachers; expansion of teaching activities in educational institutions.